SISTEM TATA RUANG DESA TRADISIONAL BATAK TOBA DAN RELEVANSINYA DI KAWASAN DANAU TOBA (ANALISIS SOSIOLOGIS) - Harisan Boni Firmando (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2023)
The main purpose of establishing a village is to meet the needs of the community that founded the village. In order for the community's needs to be met, it is necessary to manage the village potential properly. The purpose of this study was to determine the spatial system of the traditional Batak Toba village which includes the physical and social components of the traditional Batak Toba village and how the social system organizes the physical and social components of a village. This study uses qualitative methods to understand social phenomena. The results of the study indicate that a village for the Toba Batak community is a social order and system in which the community can interact socially, both between individuals and between families. The traditional Batak Toba village is autonomous and has authority. In order for the autonomy and authority of a village to continue to exist, a traditional Batak Toba village lives in a legal order. The running of the legal system is organized by a collective leadership in a village, this collective leadership creates a legal order and a place for community questions. In the event of a violation or dispute, the collective leadership is asked for consideration of the sanctions or penalties that will be given.